Chilli thrips, Scirtothrips dorsalis Hood (Thysanoptera: Thripidae) Management Practices for Florida Strawberry Crops - Gagandeep Kaur; Sriyanka Lahiri (EDIS)
This publication provides current management practices for chilli thrips in both conventional and organic strawberries as a guide for Extension agents and growers.